P20 Obeticholic acid improves experimental non-invasive markers of non-alcoholic steatohepatitis and advanced fibrosis: results of a secondary analysis from the month-18 interim analysis of the REGENERATE study. (28th September 2020) - Digpal, Kuldip; Anstee, Quentin
Abstract : In the REGENERATE 18-month interim analysis, obeticholic acid (OCA) improved surrogate endpoints of liver fibrosis in patients with non-alcoholic steatohepatitis (NASH). New biomarker indices are being developed, including FibroMeter (FM), which is designed to predict fibrosis stage ≥2 using age, gender, alpha-2-macroglobulin, international normalized ratio, platelets, urea, and gamma-glutamyltransferase. FM Vibration-Controlled Transient Elastography (VCTE) uses the same biomarkers (excluding urea) with liver stiffness (LS). The FibroScan AST (FAST™) score uses LS by VCTE, Controlled Attenuation Parameter score, and aspartate aminotransferase to identify patients with NASH and NAFLD Activity Score (NAS) ≥4 and fibrosis stage ≥2. NASH patients with fibrosis stages 2 and 3 were randomized (1:1:1) to placebo (N=311), OCA 10 mg (N=312), or OCA 25 mg (N=308) once daily. Changes in FM (N=604), FM VCTE (N=604), and FAST (N=391) were analyzed using a mixed-effect repeated measures model (MRMM), with factors of treatment, baseline, visit, visit-by-treatment interaction, and stratification. Least square means and p-values were based on MMRM. At baseline, no significant differences were observed in scores across treatment groups (figure 1 ). Patients with stage 3 fibrosis at baseline had higher scores than those with stage 2 fibrosis. OCA-treated patients experienced improvements in FM, FM VCTE, and FAST at Month 6 through Month 18. No improvements were observed with placebo (figure 1 ). OCA treatment resulted in early and sustained improvements in non-invasive assessments of fibrosis in NASH. Improvements in FM and FM VCTE are consistent with OCA's anti-fibrotic effect, while improvements in FAST are consistent with amelioration of NASH inflammation and fibrosis.